Indigenous Community-Friendly Tourism Development Strategy Through Governance Approach - Tresiana, Novita; Rahmat Sanjaya; Noverman Duadji (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2023)
The study introduces a governance approach in indigenous peoples-friendly tourism development strategy. It describes the policy process to strengthen the quality of governance. The study uses original empirical data from West Tulang Bawang Regency, specifically 2 traditional villages, to answer one main question: to find the factors that influence the performance of indigenous peoples-friendly tourism development in relation to the policy process. Analysis of the study is directed at how institutional-level processes and organizational-managerial governance levels influence the development of tourism policies that are friendly to indigenous peoples. The study uses qualitative methods, using 18 respondents. The study found that key factors in development included a value system in the form of a village law policy and the SDGs Agenda, a green approach, and a green tourism village program. Paying attention to and building collaboration with key stakeholders, namely indigenous-local communicators can build synergy of knowledge and discourse, actors and networks, politics and interests in the policy process. Benefits are obtained through increased governance capacity.